Análise de um processo de projeto industrial de mineração com foco na validação para compatibilização dos modelos BIM (Building Information Modeling) - Alexandre de Almeida Vasconcelos (2019)
The use of the automatic ruleset in projects developed using BIM, optimizes the process of design review and coordination of projects. The range of functionalities of BIM model check platforms increases every year, which makes the choice of this platform, by those involved in the project, a task that must be based on a plan that analyzes the entire chain of an enterprise. This research aimed to analyze an industrial design modeling process developed with BIM tools. Along with the analysis of the modeling of each discipline, the process of information exchange between them and the processes of design review / model checking and BIM coordination were evaluated. In addition, an improvement of the current process was proposed, with a set of automatic rule checking focused on the detection and classification of hardclash among BIM components. The project analised is from the mining segment, and it is in the detail design phase with BIM components at Level of Development (LOD) 400. Those involved at the beginning of the project decided for the adoption of Autodesk technology in the fields of: modeling, verification and coordination of projects. In addition to the use of applications, with the intent for full interoperability between the models and processes, applications and plug-ins ,using Application Programming Interface (API), were developed by project stakeholders,. The present work use the Constructive Research method. In this context, the participation of the researcher in the project process did not interfere with the analyzes carried out, on the contrary, it facilitated the data obtainement, problem notion / domain and suitable propositions. The construct of this research resulted in an improvement of the design review, model check and coordination processes in all tests performed, reducing 48% of the total time of verification, classification and definition of corrections over all the hardclash interferences.